Mechanism of Action and Therapeutic Potential of the β-Hairpin Antimicrobial Peptide Capitellacin from the Marine Polychaeta Capitella teleta - Victoria N. Safronova; Pavel V. Panteleev; Stanislav V. Sukhanov; Ilia Y. Toropygin; Ilia A. Bolosov; Tatiana V. Ovchinnikova (Marine Drugs, 2022)
Among the most potent and proteolytically resistant antimicrobial peptides (AMPs) of animal origin are molecules forming a β-hairpin structure stabilized by disulfide bonds. In this study, we investigated the mechanism of action and therapeutic potential of the β-hairpin AMP from the marine polychaeta Capitella teleta, named capitellacin. The peptide exhibits a low cytotoxicity toward mammalian cells and a pronounced activity against a wide range of bacterial pathogens including multi-resistant bacteria, but the mechanism of its antibacterial action is still obscure. In view of this, we obtained analogs of capitellacin and tachyplesin-inspired chimeric variants to identify amino acid residues important for biological activities. A low hydrophobicity of the β-turn region in capitellacin determines its modest membranotropic activity and slow membrane permeabilization. Electrochemical measurements in planar lipid bilayers mimicking the E. coli membrane were consistent with the detergent-like mechanism of action rather than with binding to a specific molecular target in the cell. The peptide did not induce bacterial resistance after a 21-day selection experiment, which also pointed at a membranotropic mechanism of action. We also found that capitellacin can both prevent E. coli biofilm formation and destroy preformed mature biofilms. The marked antibacterial and antibiofilm activity of capitellacin along with its moderate adverse effects on mammalian cells make this peptide a promising scaffold for the development of drugs for the treatment of chronic E. coli infections, in particular those caused by the formation of biofilms.